A formação de professores de matemática para atender alunos com deficiência intelectual: uma análise dos microdados do censo escolar - Jungo, Brisa Gama (2022)
The training of teachers in the inclusive perspective still proves to be challenging as the classroom presents a rich diversity, awakening to teachers the need to improve their training, both initial and continuing. The specificities demand from the teacher the recognition, acceptance and respect for the difference present in the school context as well as adequate preparation, aligning theory and pedagogical practice, for the development of effective methods in serving students with special educational needs and/or some type of disability, thus promoting not only access to these students in regular education, but ensuring quality education for all. In this sense, this work established an analysis of the training of mathematics teachers about Special Education from the perspective of Inclusive Education and, on the other hand, on the effective enrollment of Special Education students, based on the collection of information in the microdata of the school census, in the state of São Paulo in the years 2010, 2015 and 2020. Our analyzes were based on the assumptions of the Historical Cultural Theory that allows us to understand human development, on the Historical-Critical Pedagogy that allows us to establish relationships with the training and performance of teachers and on Historical and Dialectical Materialism that brought support for the apprehension of quantitative data in its material and historical context. We conclude that training, especially the initial one, must bring inputs to make the teaching and learning process in mathematics possible in an inclusive perspective, aligning pedagogical practice with scientific knowledge and that continuing education, in turn, must complement the initial and not supply possible flaws of this process. Furthermore, although historical changes in legislation are evident, it is urgent to review policies for inclusive education and teacher training, as well as breaking stigmatized perceptions about the role of teachers and the special education public.